2022
DOI: 10.1186/s13287-022-03007-7
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells attenuate acne-related inflammation via suppression of NLRP3 inflammasome

Abstract: Background Acne is a chronic facial disease caused by Propionibacterium acnes, which proliferates within sebum-blocked skin follicles and increases inflammatory cytokine production. Several therapeutic drugs and products have been proposed to treat acne, yet no single treatment that ensures long-term treatment efficacy for all patients is available. Here, we explored the use of facial autologous fat transplant of adipose-derived stem cells (ADSCs) to dramatically reduce acne lesions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…For instance, Zhao et al demonstrated that the injection of autologous subdermal stromal vascular fraction gel (SVF) into facial areas, significantly attenuated P. acnes -related inflammation 22 . Besides, Li et al demonstrated that the local injection of ADSCs inhibited P.acnes -related inflammation by inhibiting IL-1β secretion of macrophages in mouse ears 16 . These two papers mainly elucidate that ADSCs and containing-ADSCs SVF, were able to inhibit acne vulgaris feature by modulating the microenvironmental inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Zhao et al demonstrated that the injection of autologous subdermal stromal vascular fraction gel (SVF) into facial areas, significantly attenuated P. acnes -related inflammation 22 . Besides, Li et al demonstrated that the local injection of ADSCs inhibited P.acnes -related inflammation by inhibiting IL-1β secretion of macrophages in mouse ears 16 . These two papers mainly elucidate that ADSCs and containing-ADSCs SVF, were able to inhibit acne vulgaris feature by modulating the microenvironmental inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h, the P. acnes + ADSCs group was subcutaneously injected with 50 μL ADSC suspension (10 8 /mL in PBS) into the middle of the auricle. The specific concentrations of P. acnes and ADSC were determined on the basis of previous studies 15 , 16 . For comparison, the control and P. acnes groups were injected with 50 μL PBS.…”
Section: Methodsmentioning
confidence: 99%